ỨNG DỤNG KĨ THUẬT DNA VÀO VIỆC ĐÁNH GIÁ MỐI QUAN HỆ DI TRUYỀN TẬP ĐOÀN CÂY GỖ TRẮC ĐỎ (DALBERGIA COCHINCHINENSIS) Ở VIỆT NAM ĐANG CÓ NGUY CƠ TUYỆT CHỦNG - Hiền, Vũ Thị Thu; Phòng, Đinh Thị (Vietnam Journal of Science and Technology, 2012)
AMPLICATION OF DNA TECHNIQUE IN DIVERSITY ANALYSIS OF ENDANGERED RARE RED WOOD (DALBERGIA COCHINCHINENSIS) GERMPLASM IN VIETNAM Dalbergia cochinchinensis is a rare wood tree species at risk and threatened with extinction due to economic and trade value high. RAPD and ISSR techniques were used to study  the genetic relationship of 35 DNA samples collected from JokDon National Park (Dak Lak province) and Kbang (Gia Lai province). A total of 51 primers were used (23 ISSR and 28 RAPD), there were 31/51 primers revealed polymorphic with PIC value varying from 0 (IS8, OPD03,...) to 0.423 (P63). Among 163 fragments were amplified, of which 99 were polymorphic (accounting for 60.74%). Genetic similarity coefficients between 35                           D. cochinchinensis samples ranged from 0.655 (Dc5 and Dc30) to 0.942 (Dc10 and Dc11). The pattern of grouping in the dendrogram divided 35 D.cochinchinensis samples into 2 main groups and have the genetic variation coefficients about 5.1% (1 - 0.949) to 29.3% (1 - 0.707). The first group include the only Dc9 sample have the genetic variation coefficient about 29.3% (1 - 0.707). The second group  included 34 samples remaining with the genetic variation coefficient about 5.1% (1 - 0.949) to 26.0% (1 - 0.740).